Pengaruh Kecanggihan Teknologi Informasi, Partisipasi Manajemen Dan Budaya Organisasi Terhadap Sistem Informasi Akuntansi - Vyandha Angelisa Handina Wardhani; Cris Kuntadi; Rachmat Pramukty (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
In a scientific article, previous research is very important. Previous or ongoing research contributes to the improvement of hypotheses as well as phenomena regarding the link or impact between variables. Accounting Information System literature analysis is used to analyze aspects that affect Accounting Information Systems, in particular, Information Technology Sophistication, Management Participation, and Organizational Culture. This article aims to develop hypotheses that can be used in future research regarding the influence of various variables. This literature review produces findings that as follows: Information Technology sophistication affects Accounting Information Systems, Management Participation affects Accounting Information Systems, Organizational Culture affects Accounting Information Systems.